Unknown, Unnoticed, Unheard İlahiler: Turkish-Christian Hymnody as Liturgical Theology - Perigo, Jeremy (2025)
For the estimated 5–8,000 Turkish Evangelical Christians, challenges surrounding religious identity in this Muslim-majority context are particularly evident in corporate Christian worship, where indigenous local expressions of worship and matters of faith formation can, at times, create a sense of divided dual belonging. Questions of corporate identity go beyond the simple binary comparisons of Christian versus Muslim, Western versus indigenous, or local versus global, and include layers of influences and meanings. Using data collected during Spring 2019 of the congregational song repertoires of five diverse Turkish Protestant communities, we shall seek to examine the public meaning of liturgical texts (i.e., the songs sung) to elucidate the ways Turkish-Christian communities express their beliefs through the most popular public corporate worship songs (ilahiler). The thematic analysis of this lyrical theology will then be compared with devotional meanings in the Turkish Muslim-majority. Additional comparisons are made via data collected through the Worship Leader app (Turkish), and USA and UK CCLI lists. This paper centers on liturgical theology as expressed through evangelical worship hymnody in a Christian-minority context, where much research is needed.
Keywords: Contextualization; liturgical identity; Missiology; Hymnody; repertoire studies; Congregational Song; evangelical worship; contemporary Christian worship music; Liturgical Theology; Turkish Christianity